The effect of a discrimination task on L2 learners' recall of collocations and compounds. (15th July 2013) - Boers, Frank; Eyckmans, June; Lindstromberg, Seth
Abstract : This paper reports an experiment in which 24 two‐word phrases (collocations and compounds) were dictated to 38 adult EFL students who were then asked to discriminate between ones which manifest consonant repetition across the two words (e.g. p rivat ep rop ert y ; imp ortant p oint, ) and ones which do not (e.g. private collection ; important thing ). The students' ability to recall the phrases was subsequently gauged in unannounced tests. Phrases that were judged by the students to meet the criterion (i.e. +consonant repetition) were significantly better recalled in the post‐test regardless of whether their judgement was correct. The finding that a discrimination activity results in superior recall of items that are thought to display a stipulated trait over those that do not is relevant for the experimental study of memory and can be exploited in second language instruction.